PERAN DAN STRATEGI TENAGA PENDIDIK DALAM MENDIDIK KARAKTER MODERAT BERAGAMA DI SMPIT SALMAN ALFARISI YOGYAKARTA - Ahmad Bayu Permana; Muh. Wasith Achadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the urgency of strengthening religious moderation amidst increasing cases of intolerance and exposure to radical ideologies in educational institutions. The focus of this study is to identify and analyze the roles and strategies of educators at SMPIT Salman Alfarisi Yogyakarta in instilling religious moderate characters in students. The method used is qualitative field research through in-depth interviews with the principal, vice-principals, and Islamic Religious Education teachers. The results indicate that the implementation of religious moderation is at an early stage of value internalization, focusing on social tolerance and respect for differences. Educators perform educational, habituation, role-modeling, and persuasive value reinforcement roles. Strategies applied include integration in the formal curriculum, experiential learning, and indirect strategies through school culture. The main challenges lie in the homogeneous school environment and the absence of a systematically structured special program